2012
DOI: 10.1590/s1983-14472012000400003
|View full text |Cite
|
Sign up to set email alerts
|

Arquétipos do conjunto de dados essenciais de enfermagem para atendimento de portadoras de endometriose

Abstract: This study aimed to develop an Essential Data Set for Nursing Care of Patients with Endometriosis (CDEEPE), represented by archetypes. An exploratory applied research with specialists' participation that was carried out at Heath Informatics Laboratory of PUCPR, between February and November of 2010. It was divided in two stages: CDEEPE construction and evaluation including Nursing Process phases and Basic Human Needs, and archetypes development based on this data set. CDEEPE was evaluated by doctors and nurses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…15 Consolidated criteria for reporting qualitative studies steered the designing and reporting of this study. 16 The following inclusion criteria were applied to constitute the NursingOntos group: T A B L E 1 Delusion' scoping review main results (data, diagnoses, and interventions addressing delusion), 1 Gonçalves et al 8…”
Section: Focus Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Consolidated criteria for reporting qualitative studies steered the designing and reporting of this study. 16 The following inclusion criteria were applied to constitute the NursingOntos group: T A B L E 1 Delusion' scoping review main results (data, diagnoses, and interventions addressing delusion), 1 Gonçalves et al 8…”
Section: Focus Groupsmentioning
confidence: 99%
“…The development of a nursing clinical data model allows the systematization of the connections between the elements of the nursing process-data, diagnoses and interventions-for a given nursing focus. Clinical data models enable knowledge representation by the experts of a specific area, 1 in this case, by nurses, and allow structuring all the information related to a given concept. 2 They provide evidence-based data elements related to nursing care, which may contribute to information exchange, clinical decision support, quality reporting, research, and the improvement of nursing care quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that the use of data collection instruments contributes to the quality of care, as well as to decision making. 15 It has been shown that, despite numerous advances in the early detection and the possibility of symptom relief, endometriosis is still far from being cured, and there are only palliative treatments, such as surgeries and hormonal therapies, which ease the symptoms, but which are configured as longterm treatments, generating permanent discomfort in the lives of newly diagnosed women, as well as those who reported a preexisting diagnosis. 16 The importance of providing information needed by patients about the disease process, diagnosis, current treatment options and the side effects of medications is emphasized.…”
Section: Integrative Review Articlementioning
confidence: 99%
“…Estudos nacionais (Barra, Dal Sasso, 2011;Araújo, Pires, Bandeira, 2014) e internacionais (Rasmussen, Rosenbeck, 2011;Kim, Chung, Wang, Jiang, 2014;Hannah, White, Nagle, Pringle, 2009;Kim, Coenen, Hardiker, 2012;Sweeney, 2010;Anderson, Keenan, Jones, 2009) No Brasil, alguns estudos evidenciam que conjuntos de dados mínimos de enfermagem são importantes para o desenvolvimento e planejamento dos serviços, possibilitam a construção de bases para a evolução dos métodos de pesquisa e avaliação relacionada à prática de enfermagem (Spigolon, Moro 2012). Como ferramenta de suporte para a prática profissional, permite que a coleta e análise dos dados sejam transformadas em informação para a área de conhecimento, além de documentar e viabilizar a obtenção de resultados de enfermagem esperados frente ao cuidado prestado junto aos trabalhadores (Silveira, Marin 2006).…”
Section: Padrões De Dados E Terminologias Em Saúdeunclassified